Desain Kendaraan Disabilitas Pengguna Kursi Roda - Oktriadi, Yudi; Rodika, Rodika; Subkhan, Subkhan; Fricilya, Anita; Putra, Gian Pratama; Harianto, Harianto (Manutech : Jurnal Teknologi Manufaktur, 2024)
The rate of transportation development in Indonesia faces a significant increase. However, the increase in transportation rates is not in line with the increase in residents, especially for people with disabilities. One form of discrimination against people with disabilities is the lack of accessible transportation equipment for wheelchair users. The lack of service facilities makes people with disabilities feel insecure. The lack of facilities provided makes people with disabilities choose to use individual vehicles to continue activities like normal people. The purpose of the research on providing transportation facilities for people with leg disabilities is very much needed in carrying out daily activities easily and without obstacles. The design of a wheelchair user disability vehicle uses the VDI 2222 design method with 4 stages, namely planning, conceptualizing, designing, and completing. From the conceptualization session, 3 design concept variations were generated which were then assessed based on technical and economical aspects. From the test results that were tested, the average speed that can be reached by this wheelchair user disability vehicle is 30 kilometers / hour.